The Analysis of The Role of Educational Management in Enhancing The Academic Achievement of Students at SMP Maha Putra Tello Makassar - wiwi, Dwiyanti; Linda, Nur Aslindawaty (Jurnal Pedagogi dan Inovasi Pendidikan, 2025)
Educational management is a key factor in improving the quality of the learning process and student achievement. The school principal holds a strategic role in planning, organizing, implementing, and supervising all educational activities to achieve optimal learning outcomes. This study aims to analyze the role of school management in enhancing student academic achievement at SMP Maha Putra Makassar. The research employs a descriptive qualitative and quantitative approach. Data were collected through observation, in-depth interviews, and supporting documentation. Student learning outcome improvements were measured using Normalized Gain (N-Gain) analysis. The collected data were then analyzed descriptively in the form of narratives that describe the actual conditions in the field. The results indicate that effective school management at SMP Maha Putra Tello Makassar contributes significantly to the improvement of student academic achievement. Furthermore, the implementation of structured management and continuous supervision plays an important role in fostering the optimal development of students’ academic potential. These findings underscore the importance of consistent and adaptive educational management as a determining factor in the success of the learning process at the junior high school level.